Postgraduate pedagogy in pandemic times: Online forums as facilitators of access to dialogic interaction and scholarly voices - Mendelowitz, B.; Fouche, I.; Reed, Y.; Andrews, G.; Vally Essa, F. (South African Journal of Higher Education, 2022)
In 2020, when the switch to remote teaching and learning required redesigning asynchronous on-line versions of face-to-face courses, we were concerned about whether access to engaged and dialogic learning could be facilitated in this new space. In attempting to address this concern we asked students in a B Ed Honours course to post, in an online forum, their reflective responses to weekly readings and to each other’s posts. This discussion forum became the engine of the course. With their permission, the posts of students in the 2021 cohort, together with their summative reflective reading response assignment, were analysed in order to understand different kinds of dialogic interactions and their affordances for reducing the potential alienation of asynchronous learning. One of the key findings that emerged from this analysis is the role of dialogic interaction in facilitating the development of personal, professional and scholarly voices which contributed to epistemic access. Our analysis was informed by the theoretical work of Bakhtin on the dialogic and by theoretical and empirical work of scholars in the field of critical pedagogies. We use examples from the writing of a ‘stronger’ and a ‘weaker’ student to illustrate how students negotiated roles and positions for themselves by appropriating and using the textual resources available on the forum. We argue for the value of sustained practice in ‘writing about reading’, of reading each other’s writing and of ‘writing back’ to one another on-line, for the gradual acquisition of a range of confident voices and for enhanced understanding of module content.